Design and fabrication of an intelligent irrigation control system - Algeeb, A.; Albagul, Abdulgani; Asseni, A.; Khalifa, Othman Omran; Jomah, S. Omer (2010)
This paper describes the design and fabrication of an intelligent Irrigation control system that allows intelligent control of the water applied to the field at right amounts and times. The system should have the capabilities to measure the water content in the soil so water can be applied as needed. The WATERMARK soil moisture sensor based on the measurement of the soil tension will provide the measurement of the water content. The system measures the soil tension, soil temperature and rain status and records the data in a file for future reference. It will apply water to field if a certain level of soil water tension is reached. This intelligent Irrigation control system is suitable for universities, research centers and farms where a control of the soil water content is required. The system can be used to study the water requirements for crops so irrigation can be scheduled efficiently.